Complex selection on life-history traits and the maintenance of variation in exaggerated rostrum length in acorn weevils. - Bonal, Raul; Espelta, Josep Maria; Vogler, Alfried P. (Oecologia, 2011)
Trophic interactions can trigger the development of exaggerated specialized characters and promote morphological diversification. For example, acorn weevils (genus Curculio) present strikingly long rostrums, which are used by females to perforate oviposition holes through the seed coat. Species exhibiting longer rostrums are known to exploit larger acorns, and therefore rostrum length is thought to be subject to selection to match the preferred acorn type. However, rostrum length is strongly correlated with body size, and morphological divergence could result from either selection on rostrum length for optimal food exploitation or from other pressures acting on body size. We collected infested acorns at oak forests where the large Curculio elephas and the small-bodied Curculio glandium co-occur. There were no interspecific differences in adult female body size to rostrum length allometric relationships, and rostrum length is equally correlated with body size in either species. MtDNA-based species identification showed that C. glandium larvae were present within acorns of all sizes, whereas C. elephas larvae were restricted to acorns above a minimum size, irrespective of oak species. Hence, exploitation of large acorns can hardly have triggered rostrum enlargement, as the small sized C. glandium adults (with short rostrums) could perforate and oviposit in both small and large acorns. Rather, increased rostrum length is probably a by-product of the larger body sizes of individuals emerging from bigger acorns, which allow increased larval size and enhance larval survival likelihood. Summarizing, when exaggerated feeding traits co-vary with other body features, interspecific morphological variability may result from contrasting selective pressures acting on these correlated characters.
The following values have no corresponding Zotero field: accession-num: 21674207
Keywords: Body size; Curculio; Ecomorphological diversification; Quercus; Seed size; Trophic segregation